Sol–gel preparation of low oxygen content, high surface area silicon nitride and imidonitride materials. Issue 13 (2nd March 2016) - Sardar, Kripasindhu; Bounds, Richard; Carravetta, Marina; Cutts, Geoffrey; Hargreaves, Justin S. J.; Hector, Andrew L.; Hriljac, Joseph A.; Levason, William; Wilson, Felix
Abstract : Low oxygen silicon imidonitride samples are produced from Si(NHMe)4 and NH3 with NH4 OTf catalyst and structurally characterised. Abstract : Reactions of Si(NHMe)4 with ammonia are effectively catalysed by small ammonium triflate concentrations, and can be used to produce free-standing silicon imide gels. Firing at various temperatures produces amorphous or partially crystallised silicon imidonitride/nitride samples with high surface areas and low oxygen contents. The crystalline phase is entirely α-Si3 N4 and structural similarities are observed between the amorphous and crystallised materials.